2007
DOI: 10.1111/j.1445-2197.2007.04057.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Infrared Spectroscopy in Diagnosis of Acute Pancreatitis

Abstract: The successful classification of infrared spectra in patients with acute pancreatitis implies that the pathophysiology of disease alters the composition of the specimen in a characteristic fashion--in this case the serum make-up reflects the presence of acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In the diagnostic criteria of acute pancreatitis established by the Japanese Ministry of Health, Labour, and Welfare 2008 [1], a diagnosis of acute pancreatitis is made if the patient presents with at least two of the following three manifestations: acute attack of abdominal pain and tenderness in the upper abdomen, elevated levels of pancreatic leaking enzymes and findings of the pancreas detected by US, CT or MRI. Because individual cut‐off levels differ depending upon reports (Table 1) [], at present there is neither sufficient evidence nor consensus to support the setting of cut‐off levels.…”
Section: Introductionmentioning
confidence: 99%
“…In the diagnostic criteria of acute pancreatitis established by the Japanese Ministry of Health, Labour, and Welfare 2008 [1], a diagnosis of acute pancreatitis is made if the patient presents with at least two of the following three manifestations: acute attack of abdominal pain and tenderness in the upper abdomen, elevated levels of pancreatic leaking enzymes and findings of the pancreas detected by US, CT or MRI. Because individual cut‐off levels differ depending upon reports (Table 1) [], at present there is neither sufficient evidence nor consensus to support the setting of cut‐off levels.…”
Section: Introductionmentioning
confidence: 99%
“…800 and 1 1,000 nm, respectively, limits spectroscopic studies in these regions [30] . Moreover, our previous study showed that IR spectroscopy in this range successfully distinguished AP from acute abdominal disorders of extrapancreatic origin and from control specimens [31] . Before any further analysis, triplicate spectra from each patient were averaged and the median value for each wavelength was used, giving a total of 846 data points per spectrum.…”
Section: Infrared Spectroscopymentioning
confidence: 99%
“…The idea that a certain physico-chemical technique may identify changes in blood indicative of its oxidative status is not novel. For example, several years ago we pioneered the use of infrared spectroscopy (which measures the wavelengths of infrared light absorbed by a biological fluid) in patients with acute pancreatitis [23,24]. The authors chose another perspective technique, cyclic voltammetry, which is based on the analysis of the intensity of a current crossing a biological fluid over a wide range of voltages, and demonstrated that the current maxima of the first peak of a cyclic voltagram correlated with the severity of pancreatitis as well as with the concentrations of some antioxidants.…”
Section: In-vivo Studiesmentioning
confidence: 99%